Determinants of in-group bias: group affiliation or guilt-aversion? - Werner Güth; Matteo Ploner; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In-group favoritism in social dilemma situations is one of the main findings of studies in Social Identity Theory. We investigate what causes the in-group bias: is it due to mere group affiliation or, alternatively, is guilt-aversion a possible explanation? We induce group membership in a minimal group setting, observe in-/out-group transfers and elicit re- spective beliefs. We find that mere group affiliation affects beliefs and explains a substantial part of the bias, but we also find evidence in favor of guilt-aversion as a source of motivation.
Keywords: C72; D01; C91; C92; D84; 330; Social preferences; experiments; social dilemma; group identity; guilt aversion; Soziale Gruppe; Persönlichkeitspsychologie; Bias; Soziale Wohlfahrtsfunktion; Gefangenendilemma; Test